Fossil woods (Coniferales) from the Baqueró Group (Aptian), Santa Cruz Province, Argentina - Vera, Ezequiel Ignacio (2012)
Two new conifer morphospecies represented by a secondary xylem are reported for the Lower Cretaceous Baqueró Group (Santa Cruz Province, Argentina). Agathoxylon sp. is characterized by poorly defined growth rings, predominantly uniseriate pitting in the radial wall of the tracheids, cross fields with 1-6 pits and uniseriate rays. These features are shared with the leafy branches described for the unit as Araucaria grandifolia Feruglio emend. Del Fueyo and Archangelsky. The second taxon, Brachyoxylon sp. cf. B. boureaui, possesses poorly defined growth rings, mixed wood with predominantly uniseriate radial pitting, cross fields with 8-26 pits and uniseriate rays. These taxa represent the first fossil woods described for Baqueroan strata.